2005
DOI: 10.1007/bf03216825
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the prevalence and seriousness of academic dishonesty in Australian universities

Abstract: Academic dishonesty is a fundamental issue for the academic integrity of higher education institutions, and one that has lately been gaining increasing media attention. This study reports on a survey of 1206 students and 190 academic staff across four major Queensland universities in relation to student academic misconduct. The aim of the survey was to determine the prevalence of academic misconduct, and to investigate the extent to which perceptions of dishonesty are shared between students and staff, as prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
183
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 24 publications
12
183
1
15
Order By: Relevance
“…Without a thorough investigation of these questionnaires' psychometric properties, however, it remains unclear what construct(s) are being measured and whether the questions are measuring these construct(s) in a consistent way across respondents. Despite this, the majority of recently published Australian plagiarism studies omit any discussion of the psychometric properties of the measures adopted (Brimble and Stevenson-Clarke, 2005;Egan, 2008;Ryan et al, 2009;Sheard et al, 2002;Song-Turner, 2008;Yeo, 2008). Thus, despite the often-extensive sample sizes and potentially important results of these studies, the lack of reliability checks cast doubt on any interpretation of the findings.…”
Section: Issues With Omitting Psychometric Analysis When Measuring Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a thorough investigation of these questionnaires' psychometric properties, however, it remains unclear what construct(s) are being measured and whether the questions are measuring these construct(s) in a consistent way across respondents. Despite this, the majority of recently published Australian plagiarism studies omit any discussion of the psychometric properties of the measures adopted (Brimble and Stevenson-Clarke, 2005;Egan, 2008;Ryan et al, 2009;Sheard et al, 2002;Song-Turner, 2008;Yeo, 2008). Thus, despite the often-extensive sample sizes and potentially important results of these studies, the lack of reliability checks cast doubt on any interpretation of the findings.…”
Section: Issues With Omitting Psychometric Analysis When Measuring Atmentioning
confidence: 99%
“…For instance, Gururajan and Roberts (2005) found that no reliability checks were undertaken on the questionnaire instruments used in plagiarism studies in Australia. Further studies (e.g., Brimble and Stevenson-Clarke, 2005;Egan, 2008;Marshall and Garry, 2005;Ryan et al, 2009;Sheard et al, 2002;Song-Turner, 2008;Yeo, 2008) support this assertion. Each of these studies utilised survey instruments to quantify perceptions and attitudes toward plagiarism, yet the basic psychometric properties of the instruments used were not reported.…”
mentioning
confidence: 93%
“…Brimble and Stevenson-Clarke 2005;Marsden et al 2005;Ogilvie and Stewart 2010). While research has been conducted on academic dishonesty amongst criminology students in the United States (Coston and Jenks 1998;Eskridge and Ames 1993;Lambert and Hogan 2004;Tibbetts 1998), to date no research has been conducted on academic dishonesty within the specific context of Australian university students within criminal justice and policing disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…While research has been conducted on academic dishonesty amongst criminology students in the United States (Coston and Jenks 1998;Eskridge and Ames 1993;Lambert and Hogan 2004;Tibbetts 1998), to date no research has been conducted on academic dishonesty within the specific context of Australian university students within criminal justice and policing disciplines. This is unfortunate, as data from other countries with different socio-historical contexts may not be directly generalizable to the Australian context (Brimble and Stevenson-Clarke 2005). In addition, given the significant focus on misconduct and corruption within policing and criminal justice agencies in Australia as a result of government enquiries (see Lewis et al 2010), the lack of research into unethical conduct among policing and criminal justice students in Australia is surprising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation